Mobile genetic elements associated with carbapenemase genes in South American Enterobacterales - Reyes,Jorge Aníbal (2020)
ABSTRACT Introduction: Carbapenem resistance in members of order Enterobacterales is a growing public health problem causing high mortality in developing and industrialized countries. Its emergence and rapid propagation worldwide was due to both intercontinental spread of pandemic strains and horizontal dissemination via mobile genetic elements (MGE) such as plasmids and transposons. Objective: To describe MGE carrying carbapenem resistance genes in Enterobacterales which have been reported in South America. Search strategy and selection criteria: A search of the literature in English or Spanish published until 2019 in PubMed, Google Scholar, LILACS and SciELO databases was performed for studies of MGE in Enterobacterales reported in South American countries. Results: Seven South American countries reported MGE related to carbapenemases. Carbapenemase-producing Klebsiella pneumoniae belonging to clonal complex 258 were the most prevalent pathogens reported; others carbapenemase-producing Enterobacterales such as Escherichia coli, Serratia marcescens, and Providencia rettgeri also have been reported. The MGE implicated in the spread of the most prevalent carbapenemase genes are Tn4401 and non-Tn4401 elements for bla KPC and ISAba125 for bla NDM, located in different plasmid incompatibility groups, i.e. L/M, A/C, FII and bacterial clones. Conclusion: This review indicates that, like in other parts of the world, the most commonly reported carbapenemases in Enterobacterales from South America are being disseminated through clones, plasmids, and transposons which have been previously reported in other parts of the world.